KADAR PENGGUNAAN NALAR DALAM HUKUM KEWARISAN ISLAM - Akhmad Jalaludin (JURNAL PENELITIAN, 2014)
This study attempted to assess the level of the use of reason in the Islamic inheritance law. From this study, that use the usu}l>fiqh (Islamic legal theory) approach, it is known that inheritance law that often considered as qat}'iy (definitive) and can not be changed, in fact, is filled with provisions was formulated by using reason (ijtihad). Even some of the ijtihad is touching the provisions set forth by the verses of the Koran that considered as qat}'iy, in order to give justice to the heirs. This fact suggests that the inheritance law is a sphere that is open to be reformulated and that the consideration of justice also been and can be used although it seem contrary to the provisions of textual considered as qat}'iy.